Use of Genomic Estimated Breeding Values Results in Rapid Genetic Gains for Drought Tolerance in Maize. Issue 1 (1st March 2017) - Vivek, B.S.; Krishna, Girish Kumar; Vengadessan, V.; Babu, R.; Zaidi, P.H.; Kha, Le Quy; Mandal, S.S.; Grudloyma, P.; Takalkar, S.; Krothapalli, K.; Singh, I.S.; Ocampo, Eureka Teresa M.; et al.
Abstract : More than 80% of the 19 million ha of maize ( Zea mays L.) in tropical Asia is rainfed and prone to drought. The breeding methods for improving drought tolerance (DT), including genomic selection (GS), are geared to increase the frequency of favorable alleles. Two biparental populations (CIMMYT‐Asia Population 1 [CAP1] and CAP2) were generated by crossing elite Asian‐adapted yellow inbreds (CML470 and VL1012767) with an African white drought‐tolerant line, CML444. Marker effects of polymorphic single‐nucleotide polymorphisms (SNPs) were determined from testcross (TC) performance of F2:3 families under drought and optimal conditions. Cycle 1 (C1) was formed by recombining the top 10% of the F2:3 families based on TC data. Subsequently, (i) C2[PerSe_PS] was derived by recombining those C1 plants that exhibited superior per se phenotypes (phenotype‐only selection), and (ii) C2[TC‐GS] was derived by recombining a second set of C1 plants with high genomic estimated breeding values (GEBVs) derived from TC phenotypes of F2:3 families (marker‐only selection). All the generations and their top crosses to testers were evaluated under drought and optimal conditions. Per se grain yields (GYs) of C2[PerSe_PS] and that of C2[TC‐GS] were 23 to 39 and 31 to 53% better, respectively, than that of the corresponding F2 population. The C2[TC‐GS] populations showed superiority of 10 to 20% over C2[PerSe‐PS] of respective populations. Top crosses of C2[TC‐GS] showed 4 to 43% superiority of GY over that of C2[PerSe_PS] of respective populations. Thus, GEBV‐enabled selection of superior phenotypes (without the target stress) resulted in rapid genetic gains for DT.